Application of Management Accounting System at indonesian Startup Companies - Edward Fazri; Galih Fajar Muttaqin (FEB Universitas Sultan Ageng Tirtayasa, 2021)
This research was conducted on Indonesian startup companies. This study examines the effect of innovation on the management accounting system, the effect of the management accounting system on financial performance and examines the mediating effect of the management accounting system on the effect of innovation on financial performance. This study involved 42 Indonesian startup companies domiciled in Jabodetabek. Questionnaires were distributed to sample companies to obtain the required data and processed using smart PLS 2.0. The results of this study are that there is a significant positive effect of innovation on the management accounting system, there is a significant positive effect of the management accounting system and there is evidence that the management accounting system has a mediating effect that strengthens the influence of innovation on financial performance.